2016
DOI: 10.7554/elife.22280
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic mode of mitotic bookmarking by transcription factors

Abstract: During mitosis, transcription is shut off, chromatin condenses, and most transcription factors (TFs) are reported to be excluded from chromosomes. How do daughter cells re-establish the original transcription program? Recent discoveries that a select set of TFs remain bound on mitotic chromosomes suggest a potential mechanism for maintaining transcriptional programs through the cell cycle termed mitotic bookmarking. Here we report instead that many TFs remain associated with chromosomes in mouse embryonic stem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
348
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(379 citation statements)
references
References 55 publications
29
348
2
Order By: Relevance
“…2Y,Z). We thus conclude that detection of RNAP2 in mitotic chromatin is both antibody dependent and that cases of exclusion are likely due to fixation artifacts, as previously reported for transcription factors (Lerner et al 2016;Teves et al 2016). Importantly, the presence of an active form of RNAP2 in mitosis has been reported at the centromere (Liu et al 2015), but our observation agrees with various hints throughout the literature that it is also present at low levels throughout mitotic chromatin.…”
Section: Rna Pol II During Mitosissupporting
confidence: 91%
See 2 more Smart Citations
“…2Y,Z). We thus conclude that detection of RNAP2 in mitotic chromatin is both antibody dependent and that cases of exclusion are likely due to fixation artifacts, as previously reported for transcription factors (Lerner et al 2016;Teves et al 2016). Importantly, the presence of an active form of RNAP2 in mitosis has been reported at the centromere (Liu et al 2015), but our observation agrees with various hints throughout the literature that it is also present at low levels throughout mitotic chromatin.…”
Section: Rna Pol II During Mitosissupporting
confidence: 91%
“…Despite the physical condensation of mitotic chromosomes, global ATAC-seq profiles are highly similar between asynchronous and mitotic cells (Teves et al 2016), indicating an overall retention in accessibility at the molecular level. At a finer level, it has been shown that promoter accessibility is maintained during mitosis (Martinez-Balbas et al 1995;Hsiung et al 2015), although enhancer accessibility is lost (Hsiung et al 2015).…”
Section: Enhancer Usagementioning
confidence: 98%
See 1 more Smart Citation
“…It has been known for ~ 60 years that mitotic chromosome condensation is correlated with transcriptional repression 39,40 . Studies in the past two decades have since shown that this repression is not absolute because transcription factors can still access the interior of mitotic chromosomes [41][42][43] and because lowlevel transcription is detectable in mitotic mammalian cells [44][45][46] . In S. pombe G0 cells, we also observed a correlation between smaller nucleus size (a proxy for chromatin condensation) and transcriptional repression, in line with previous studies 8, 10 .…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, chemical fixation of cells has been demonstrated to cause artefacts in the dynamic detection of transcription factors. 30 Live-cell imaging can visualise the movement of select proteins dynamically, but is limited to transgenic cell lines, which limits multiplexing (number of targets measured concurrently).…”
Section: Introductionmentioning
confidence: 99%